A Cross Sectional Study On Urinary Microalbuminuria And Serum Uric Acid In Patients Of Type 2 Diabetes Mellitus At A Tertiary Care Hospital - Dr. Shruthi R; Dr. Sridevi HS; Dr. Sharanabasavaraja B M; Dr. Sunil Pattanshetty (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Diabetes mellitus is a chronic metabolic condition characterized by hyperglycemia, and protein and fat metabolism derangement. About 40 % of people having type 1 diabetes (T1DM) as well as 5-15 % of people with type 2 diabetes (T2DM) experience end-stage renal disease (ESRD). With this overview, this study was undertaken to assess the significance of microalbuminuria and uric acid in the early detection of renal involvement among patients with T2DM. Materials and Methods: This cross-sectional study was carried out by Department of General Medicine, Ballari Medical College and Research Centre, Ballari between January 2024 to October 2024. 300 diagnosed patients of type 2 Diabetes Mellitus in the age group of 25-75 years, coming in medicine OPD were taken as cases and 300 age and sex-matched normal persons were taken as controls. Patients with complications like retinopathy, h/o diabetic foot lesion, cardiovascular diseases, overt nephropathy, Type 1 Diabetes Mellitus, hypertension, pregnancy, urinary tract infections, acute febrile illness, patients on ACE inhibitors, on chronic NSAIDS, patients on treatment with uric acid lowering drugs or diuretics, patients having hepatic diseases or renal diseases, patients with gouty arthritis, menstruation or vaginal discharge, leukemia, myeloma, chemotherapy, radiotherapy, congestive cardiac failure or any other chronic illness were excluded from the study. Results: Out of 300 cases studied, there were 110 males and 190 females whereas there were 94 males and 206 females in controls. The mean age (years) in cases and control was found to be 52.2 ± 8.2 and 54.3 ± 9.7 respectively. The mean BMI (kg/m2) in cases and control was found to be 27.4± 6.5 and 24.3 ± 4.6 respectively. The mean fasting plasma glucose (mg/dl) in cases and control was found to be 189.7± 53.4 and 87.1 ± 10.4, respectively. The mean post meal plasma glucose (mg/dl) in cases and control was found to be 282.4 ± 89.5 and 119.6 ± 34.6, respectively. The mean urine microalbumin (mg/g creatinine) in cases and control was calculated to76.6 ± 65.5 and 22.8± 7.6, respectively. The mean serum uric acid (mg/dl) was 6.2 ± 1.2 and 4.3 ± 0.8, respectively for cases and controls. The mean serum creatinine (mg/dl) 1.2 ± 0.5 and 0.9 ± 0.7, respectively. The age group, BMI, FPG, 2hPG, urine microalbumin were higher in cases as compared to control and the difference was statistically significant (p<0.05). There was higher serum uric acid observed in cases as compared to control and the difference was statistically significant (p<0.05). There was high serum creatinine observed in cases as compared to control and the difference was statistically non-significant (p> 0.05). Conclusion: Diabetic nephropathy is amongst the most serious diabetes complications and the major cause of end-stage renal disease. Strict glycemic control, microalbuminuria monitoring, and serum uric acid monitoring with better management may delay diabetic nephropathy.